Rational information leakage - LU, Hai (Institutional Knowledge at Singapore Management University, 2014)
Empirical evidence suggests that information leakage in capital markets is common. We present a trading model to study the incentives of an informed trader (e.g., a well informed insider) to voluntarily leak information about an asset's value to one or more independent traders. Our model shows that, while leaking information dissipates the insider's information advantage about the asset's value, it enhances his information advantage about the asset's execution price relative to other informed traders. The profit impact of these two effects are countervailing. When there are a sufficient number of other informed traders, the profit impact from enhanced information dominates. Hence, the insider has incentives to leak some of his private information. We label this rational information leakage and discuss its implications for the regulation of insider trading.